2019
DOI: 10.1007/s10964-019-01107-x
|View full text |Cite
|
Sign up to set email alerts
|

Informant Discrepancies in Internalizing and Externalizing Symptoms in an At-Risk Sample: The Role of Parenting and School Engagement

Abstract: A number of studies have used variable-centered approaches to examine informant discrepancies on children's behavior problems; however, few such studies have used person-centered approaches to explore patterns of informant discrepancies or correlates of discrepancies in informant symptom ratings. The present study addressed these gaps by examining profiles of informant agreement on internalizing and externalizing symptoms and examining whether two important contextual factors, parenting and school engagement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…One limitation is the use of parentreport for only the SDQ subscales and covariates, which can produce some bias in the results. 43 The EB profiles do not represent clinical disorders. However, the SDQ has shown good predictive power for clinical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation is the use of parentreport for only the SDQ subscales and covariates, which can produce some bias in the results. 43 The EB profiles do not represent clinical disorders. However, the SDQ has shown good predictive power for clinical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The additional strengths are the large sample provided by the MCS and its national representativeness. One limitation is the use of parent-report for only the SDQ subscales and covariates, which can produce some bias in the results [45]. The EB profiles do not represent clinical disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers often spend more time during the day with children than do parents, having the opportunity to observe them in various dynamics and in interaction with other children, as well as with themselves and other adults (Abikoff et al, 1993). Moreover, teachers observe children in both structured (e.g., classroom) and unstructured (e.g., lunchroom) settings with their peers (Curhan et al, 2020; Farrell et al, 2018). Thus, teacher-reports are relevant and unique sources of information about the children’s behavior.…”
mentioning
confidence: 99%
“…Similarly, another study found that income was not related to discordance with regard to trauma-related symptom concordance (Wamser-Nanney & Campbell, 2021). Aspects of parenting, such as family cohesion, parental monitoring, communication, and lower family stress have been linked to a higher agreement in reports of non-trauma-exposed children's internalizing and externalizing symptoms (Al Ghriwati et al, 2018;Curhan et al, 2020;Kolko & Kazdin, 1993;Treutler & Epkins, 2003). However, family factors have not yet been investigated in relation to discordance in traumarelated symptom reports despite their potential relevance.…”
mentioning
confidence: 99%